Methodology and methods for media monitoring system оf Central Asia: international and national experience (Herald of Journalism, 2018)
Regional interests tend to adapt to political trends, and the media are obliged to maintain ethical standards and demands of the moment. The history of Kazakh journalism contains little-known experience of «centralization» of the media content management in the twentieth century. The autonomous status of the Kazakh Republic meant some ideological dependence on the Centre. Political trends and traditions orally controversy contributed to the emergence of journalism as a profession and industry knowledge. The author suggests that the Central Asian states will not prevent the system and methodology for monitoring the concentration of media content. Problematic issues of monitoring techniques can be studied in the framework of educational programs, journalists, students, masters and doctoral students.Key words: Central Asia, the media, Mustafa Shokai, Karim Toktabaev, journalism, the press center, Kazpredstavitelstvo, methodology.